Pengaruh Pendekatan Pembelajaran Deep Learning dan Fasilitas Sekolah terhadap Hasil Belajar Siswa MPLB SMK Negeri 14 Jakarta - Imel Ahmarita Meliana; Darma Rika Swaramarinda; Rizki Firdausi Rachmadania (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aims to determine the influence of the Deep Learning learning approach and school facilities on the learning outcomes of MPLB students at SMK Negeri 14 Jakarta. The research method used is a survey with a quantitative approach. The research population consisted of 180 MPLB vocational students, with a sample of 125 students determined through proportional stratified sampling techniques. Data collection was carried out using questionnaire instruments, while data analysis used multiple linear regression with the help of SPSS version 26 application. The analysis includes research instrument tests, classical assumption tests, and hypothesis tests. The results of the study show that there is a positive and significant relationship between the Deep Learning learning approach to student learning outcomes. In addition, school facilities have also been proven to have a positive and significant effect on learning outcomes. Simultaneously, the Deep Learning approach and school facilities together have a positive influence on the learning outcomes of MPLB students. These findings confirm that the success of learning is not only determined by the methods used, but also by the support of school facilities and infrastructure. Thus, the application of a Deep Learning approach supported by adequate school facilities can improve the quality of student learning outcomes at SMK Negeri 14 Jakarta.